Funções de predição espacial de propriedades do solo - Rosa, Alessandro Samuel (2012)
The possibility of mapping soil properties using soil spatial prediction functions (SSPFe) is a reality. But is it possible to SSPFe to estimate soil properties such as the particlesize distribution (psd) in a young, unstable and geologically complex geomorphologic surface? What would be considered a good performance in such situation and what alternatives do we have to improve it? With the present study I try to find answers to such questions. To do so I used a set of 339 soil samples from a small catchment of the hillslope areas of central Rio Grande do Sul. Multiple linear regression models were built using landsurface parameters (elevation, convergence index, stream power index). The SSPFe explained more than half of data variance. Such performance is similar to that of the conventional soil mapping approach. For some size-fractions the SSPFe performance can reach 70%. Largest uncertainties are observed in areas of larger geological heterogeneity. Therefore, significant improvements in the predictions can only be achieved if accurate geological data is made available. Meanwhile, SSPFe built on land-surface parameters are efficient in estimating the psd of the soils in regions of complex geology. However, there still are questions that I couldn t answer! Is soil mapping important to solve the main social and environmental issues of our time? What if our activities were subjected to a social control as in a direct democracy, would they be worthy of receiving any attention?